B‐cell receptors of EBV‐negative Burkitt lymphoma bind modified isoforms of autoantigens. Issue 3 (16th June 2022) - Bock, Theresa; Bewarder, Moritz; Cetin, Onur; Fadle, Natalie; Regitz, Evi; Schwarz, Eva C.; Held, Jana; Roth, Sophie; Lohse, Stefan; Pfuhl, Thorsten; Wagener, Rabea; Smola, Sigrun; et al.
Abstract: Burkitt lymphoma (BL) represents the most aggressive B‐cell‐lymphoma. Beside the hallmark of IG‐MYC ‐translocation, surface B‐cell receptor (BCR) is expressed, and mutations in the BCR pathway are frequent. Coincidental infections in endemic BL, and specific extra‐nodal sites suggest antigenic triggers. To explore this hypothesis, BCRs of BL cell lines and cases were screened for reactivities against a panel of bacterial lysates, lysates of Plasmodium falciparum, a custom‐made virome array and against self‐antigens, including post‐translationally modified antigens. An atypically modified, SUMOylated isoform of Bystin, that is, SUMO1‐BYSL was identified as the antigen of the BCR of cell line CA46. SUMO1‐BYSL was exclusively expressed in CA46 cells with K139 as site of the SUMOylation. Secondly, an atypically acetylated isoform of HSP40 was identified as the antigen of the BCR of cell line BL41. K104 and K179 were the sites of immunogenic acetylation, and the acetylated HSP40 isoform was solely present in BL41 cells. Functionally, addition of SUMO1‐BYSL and acetylated HSP40 induced BCR pathway activation in CA46 and BL41 cells, respectively. Accordingly, SUMO1‐BYSL‐ETA' immunotoxin, produced by a two‐step intein‐based conjugation, led to the specific killing of CA46 cells. Autoantibodies directed against SUMO1‐BYSL were found in 3 of 14 (21.4%), and autoantibodies against acetylated HSP40 in 1/14(7.1%) patients with sporadic Burkitt‐lymphoma. No reactivities against antigens of the infectious agent spectrum could be observed. These results indicate a pathogenic role of autoreactivity evoked by immunogenic post‐translational modifications in a subgroup of sporadic BL including two EBV‐negative BL cell lines.